2021
DOI: 10.1186/s13287-021-02553-w
|View full text |Cite
|
Sign up to set email alerts
|

Oct4-dependent FoxC1 activation improves the survival and neovascularization of mesenchymal stem cells under myocardial ischemia

Abstract: Background The administration of mesenchymal stem cells (MSCs) remains the most promising approach for cardiac repair after myocardial infarct (MI). However, their poor survival and potential in the ischemic environment limit their therapeutic efficacy for heart repair after MI. The purpose of this study was to investigate the influence of FoxC1-induced vascular niche on the activation of octamer-binding protein 4 (Oct4) and the fate of MSCs under hypoxic/ischemic conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In contrast, Oct4 deficiency completely eliminated PBMSC angiogenesis induced by β-catenin overexpression, as evidenced by decreased vascularization, reduced vascular density, and decreased β-catenin-mediated proangiogenic cytokines. Our previous study demonstrated that Oct4-dependent FoxC1 activation improves the survival and neovascularization of MSCs under myocardial ischemia 50 . All these data might reveal a novel mechanism: β-catenin ameliorated ischemia-related impairment of PBMSC-mediated angiogenesis by inducing MEndoT via an Oct4-dependent mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Oct4 deficiency completely eliminated PBMSC angiogenesis induced by β-catenin overexpression, as evidenced by decreased vascularization, reduced vascular density, and decreased β-catenin-mediated proangiogenic cytokines. Our previous study demonstrated that Oct4-dependent FoxC1 activation improves the survival and neovascularization of MSCs under myocardial ischemia 50 . All these data might reveal a novel mechanism: β-catenin ameliorated ischemia-related impairment of PBMSC-mediated angiogenesis by inducing MEndoT via an Oct4-dependent mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Oct4 plays a significant role in the survival and function of various MSCs. Our previous study showed Oct4 as an essential aspect for survival and neovascularization of MSCs in the ischemic conditions [11]. Oct4 can act as a mediator to cooperate with HIF-2α to promote proliferation and function of coronary arterial MSCs in ischemic hearts [10].…”
Section: Discussionmentioning
confidence: 99%
“…The model of myocardial Isch was established by induction of MI. MI was induced by ligating the left anterior descending coronary artery (LAD) as our previously described [10,11]. MI was confirmed by visual blanching distal to the occlusion site and by echocardiography 24 h after MI.…”
Section: Model Of Myocardial Isch and Sham Ischmentioning
confidence: 99%
See 1 more Smart Citation